An integrated approach towards achieving agility in design and development of a broken free-form object / Fahraz Ali and Boppana V. Chowda - Ali, Fahraz; V. Chowda, Boppana (Faculty of Mechanical Engineering (FKM) and UiTM Press, 2011)
This paper attempts to introduce a unified approach for design and development of a broken free-form object in order to achieve agility in the process. A combination of reverse engineering (RE), re-engineering (ReE) and rapid product development (RpD) approach has been tailored to address the design and development issues of the broken free-form object. A broken clutch shoe from a centrifugal clutch assembly is selected for demonstrating the efficacy of the proposed integrated methodology. To achieve agility in the process, RE is employed for quick recovery of technical data and re-construction of the entire part model. Subsequently, re-engineering is sustained through geometric dimensioning and tolerancing (GD&T) which is used as a validation tool for inspection/comparison of the reference and digitized parametric computer aided design (CAD) models. Furthermore integration of finite element analysis (FEA) is performed iteratively for optimization of influential factors of the part such as feature characteristics and material properties. Finally, computer aided manufacturing (CAM) system is introduced for rapid prototyping of the selected part. This process can manifest itself into similar industrial situations to achieve agility in the product design and development process so that the developed part can be distributed quickly to the customer. Design for better performance of the product in a short turnaround time is the main outcome of this research.